2002
DOI: 10.1029/2001jd000392
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Land‐Atmosphere Simulation Program (CLASP): Calibration and validation

Abstract: [1] We present a model and application designed to study the coupled land-atmosphere hydrologic cycle, following water from its inflow into a region by horizontal atmospheric transport through surface-atmosphere exchange processes and aquifer recharge to outflow as runoff and river discharge. The model includes a two-way water flow among its major reservoirs (atmosphere, vadose zone, groundwater, surface water, river). A unique feature of the model is that phreatophytic interactions are included when the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 44 publications
(60 reference statements)
5
74
0
1
Order By: Relevance
“…Luo et al, 2013), surface water and groundwater interactions (e.g. Winter, 2001;Gutowski et al, 2002;Maxwell and Miller, 2005;Yeh and Eltahir, 2005;Fan et al, 2007;Niu et al, 2007), and the interactions among these processes and with other existing processes in current LSMs (e.g. .…”
Section: Bounding Complexity: the Use Of Multiple Constraintsmentioning
confidence: 99%
“…Luo et al, 2013), surface water and groundwater interactions (e.g. Winter, 2001;Gutowski et al, 2002;Maxwell and Miller, 2005;Yeh and Eltahir, 2005;Fan et al, 2007;Niu et al, 2007), and the interactions among these processes and with other existing processes in current LSMs (e.g. .…”
Section: Bounding Complexity: the Use Of Multiple Constraintsmentioning
confidence: 99%
“…Fan et al (2013) found that 22%-32% of land globally is affected by shallow groundwater. Groundwater provides a source of water for evapotranspiration even during dry seasons or drought conditions (Yeh et al 1998;Gutowski et al 2002;Miguez-Macho and Fan 2012). In fact, some plants are highly reliant on groundwater (Orellana et al 2012;Rossatto et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some models (e.g., Gutowski et al 2002;York et al 2002) explicitly model the three-dimensional flow of groundwater, but these are computationally expensive to implement into GCMs . These have largely been implemented into regional models with finer horizontal resolution since horizontal transport is more important at these smaller scales Yeh and Eltahir 2005).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, three-dimensional (e.g., Gutowski et al 2002) and one-dimensional (i.e., models of independent soil column) (e.g., Liang et al 2003;Chen and Hu 2004;Maxwell and Miller 2005;Niu et al 2006;Fan et al 2007;Miguez-Macho et al 2007) groundwater models have been implemented in land surface models to simulate groundwater table and recharge/ discharge dynamically. Most studies reported results based on offline simulations driven by observed atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%